Patterns and Factors of Arabic Writing Errors: A Descriptive Study in Learning through the Imlā’ Mandzūr Method - Era Aprianti; Neldi Harianto; Ady Muh. Zainul Mustofa (Al-Uslub: Journal of Arabic Linguistic and Literature, 2025)
This study aims to describe in depth the patterns of errors in Arabic writing and the factors causing these errors in the use of the imla’ mandzur method in class VIII 2 at Al-Falah Islamic Junior High School in Jambi. This study is decriptive qualitative, with data collection techniques through observation, interviews, and documentation. The reserch subjects consisted of Arabic language teachers and eighth grade students. Data analysis was carried out throught the stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that there were five patterns of writing errors mare by students, namely errors in connecting letters, errors in writing hamzah qath’I, errors in reducing letters, errors in writing similar-sounding Hijaiyyah letters, and errors in wriring harakat. The factors causing these errrors include diverse educational backgrounds, lack of practice in writing Arabic, and concentration factors, namely lack of focus during learning. The implications of this study indicate that the application of the imla’ mandzur method needs to be accompanied by intensive practice and guidance so that students are able to write letters or spellings in Arabic according to the correct writing rules, as well as providing input for teachers to improve the effectiveness of Arabic writing intruction in schools. This research also contributes to improving students’ accuracy and motivation in Arabic writing.